Existence, uniqueness and stability of solutions to a delay hematopoiesis model: Positive periodic solutions to a delay hematopoiesis model - Bouakkaz, Ahlème; Khemis, Rabah (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
This work aims to investigate a delay hematopoiesis model where the delay depends on both the time and the current density of mature blood cells. Based on the Banach contraction principle, the Schauder's fixed point theorem and some properties of a Green's function, we establish several interesting existence and uniqueness results of positive periodic solutions for the proposed model. The derived results are new and generalize some previous studies.